The Effectiveness of Wall Pass Training Variations on Improving the Accuracy of Inside Foot Passing in SSB Cikedondong Players - Fadil Fadlurohman; Indra Safari; Adang Sudrazat (Journal Coaching Education Sports, 2026)
Passing is one of the fundamental techniques in soccer that greatly influences team play effectiveness and ball possession. However, the passing accuracy of youth soccer players still requires improvement through effective and varied training methods. This study aimed to determine the effect of varied wall pass training on improving inside-foot passing accuracy among players of SSB Cikedondong. The study employed a quantitative experimental method using a One Group Pretest-Posttest Design. The sample consisted of 15 players selected through purposive sampling. The treatment program was conducted over 12 training sessions. The research instrument used an inside-foot passing accuracy test adapted from Nurhasan (2001). Data were analyzed using descriptive statistics, normality tests, and paired sample t-tests with IBM SPSS Statistics. The results showed that the average pretest score increased from 3.07 to 5.80 in the posttest. Hypothesis testing indicated a significance value of 0.000 < 0.05, meaning that varied wall pass training had a significant effect on improving inside-foot passing accuracy. This study highlights that varied and repetitive wall pass training can effectively improve coordination, ball control, and passing precision among youth soccer players.